Hematology of Osphronemus goramy Fed with Fermented Vegetable Waste with Cows Rumen - Ilka, Ade Hidayat; Lukistyowati, Iesje; Riauwaty, Morina (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2024)
Vegetables in chicory and cabbage contain flavonoid compounds, alkaloids, saponins, glycosides, vitamin C, glucosinolates, glutamine, and sulforaphane, which have antimicrobial activity that can be used as immunomodulators that can strengthen the immune system. This research was conducted from February to April 2022 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Universitas Riau. This study aimed to analyze the effect of fermenting mustard and cabbage waste flour in artificial feed on goramy hematology. The method used is an experimental method using a one-factor Completely Randomized Design (CRD) with five treatment levels and three replications. The treatments were P0 (Feed without added fermented chicory and cabbage and challenge with Aeromonas hydrophila), and fish were fed with fermented chicory and cabbage with doses of P1 (15%), P2 (25%), P3 (35%), P4 (45%) and challenged with A. hydrophila. Fishes were reared for 60 days with feed containing fermented chicory and cabbage, and the final data was 14 days of testing with A. hydrophila with the same feed. The results showed that the best dose of feed containing fermented chicory and cabbage was in treatment P2 (25%) with a total erythrocyte of 2.21 x106 cells/mm3, a hemoglobin level of 5.40 g/dL, and a hematocrit value of 38.67%. Tested with A. hydrophila bacteria, total erythrocytes 2.68 x106 cells/mm3, hemoglobin 6.60 g/dL, hematocrit value 39.00%, survival rate 96, 67%, absolute weight growth 1.06 g. Data obtained on O. goramy fed with fermented vegetable waste with cows' rumen showed an effect on improving fish hematology.